A Bimetallic Zn/Fe Polyphthalocyanine‐Derived Single‐Atom Fe‐N4 Catalytic Site:A Superior Trifunctional Catalyst for Overall Water Splitting and Zn–Air Batteries. Issue 28 (30th May 2018) - Pan, Yuan; Liu, Shoujie; Sun, Kaian; Chen, Xin; Wang, Bin; Wu, Konglin; Cao, Xing; Cheong, Weng‐Chon; Shen, Rongan; Han, Aijuan; Chen, Zheng; Zheng, Lirong; et al.
Abstract: Developing an efficient single‐atom material (SAM) synthesis and exploring the energy‐related catalytic reaction are important but still challenging. A polymerization–pyrolysis–evaporation (PPE) strategy was developed to synthesize N‐doped porous carbon (NPC) with anchored atomically dispersed Fe‐N4 catalytic sites. This material was derived from predesigned bimetallic Zn/Fe polyphthalocyanine. Experiments and calculations demonstrate the formed Fe‐N4 site exhibits superior trifunctional electrocatalytic performance for oxygen reduction, oxygen evolution, and hydrogen evolution reactions. In overall water splitting and rechargeable Zn–air battery devices containing the Fe‐N4 SAs/NPC catalyst, it exhibits high efficiency and extraordinary stability. This current PPE method is a general strategy for preparing M SAs/NPC (M=Co, Ni, Mn), bringing new perspectives for designing various SAMs for catalytic application. Abstract : Single‐atom catalyst : A polymerization–pyrolysis–evaporation (PPE) strategy was developed to synthesize N‐doped porous carbon (NPC) with anchored atomically dispersed Fe‐N4 sites. This material is a superior trifunctional catalyst for overall water splitting and Zn–air batteries. The PPE method is a general strategy for preparing M SAs/NPC (M=Fe, Co, Ni, Mn) materials.